Turing Learning Machines - Vincenzo Ambriola (Substantia, 2024)
Alan Mathison Turing was born in London on June 23rd, 1912. In 1934, he graduated with top marks from King’s College, University of Cambridge, and in 1936, he obtained his Ph.D. from Princeton University, located in New Jersey, USA. In 1940, he worked at Bletchley Park for the Communications Department, using the Colossus machine to decipher Nazi codes. After the war, he moved to the National Physical Laboratory in Teddington, near London. In 1947, he returned to the University of Cambridge, and in 1951, he went to the University of Manchester.